2014
DOI: 10.1590/s1517-83822014000100038
|View full text |Cite
|
Sign up to set email alerts
|

Newly-synthesized chalcones-inhibition of adherence and biofilm formation of methicillin-resistant Staphylococcus aureus

Abstract: Biofilm formation and adherence of bacteria to host tissue are one of the most important virulence factors of methicillin-resistant strains of Staphylococcus aureus (MRSA). The number of resistant strains is seriously increasing during the past years and bacteria have become resistant, not only to methicillin, but also to other commonly used antistaphylococcal antibiotics. There is a great need for discovering a novel antimicrobial agent for the treatment of staphylococcal infections. One of the most promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
2
11
0
2
Order By: Relevance
“…pylori urease indicated that 4′,7,8‐trihydroxy‐isoflavene ( 141 ) was the most active compound with IC 50 0.85 mM, which was 20‐fold more potent than standard urease inhibitor (acetohydroxamic acid; Xiao et al, ). Bozic, Milenkovic, Ivkovic, and Cirkovic () reported that among three newly synthesized chalcones with OH at positions 2, 3, and 4 of B ring of 1,3‐bis‐(2‐hydroxy‐phenyl) ( 145 ; with hydroxy group in position 2) exhibited significant effect on adherence and biofilm formation of MRSA strains. In the synthetic fluoroquinolone‐flavonoid hybrids, naringenin‐ethylidene‐ciprofloxacin ( 146 ; with cyclopropan on the N atom) was the most active compound and showed eightfold to 88‐fold more potent activity than the standard drug ciprofloxacin against E .…”
Section: Synthetic Derivatives Of Flavonoidsmentioning
confidence: 99%
“…pylori urease indicated that 4′,7,8‐trihydroxy‐isoflavene ( 141 ) was the most active compound with IC 50 0.85 mM, which was 20‐fold more potent than standard urease inhibitor (acetohydroxamic acid; Xiao et al, ). Bozic, Milenkovic, Ivkovic, and Cirkovic () reported that among three newly synthesized chalcones with OH at positions 2, 3, and 4 of B ring of 1,3‐bis‐(2‐hydroxy‐phenyl) ( 145 ; with hydroxy group in position 2) exhibited significant effect on adherence and biofilm formation of MRSA strains. In the synthetic fluoroquinolone‐flavonoid hybrids, naringenin‐ethylidene‐ciprofloxacin ( 146 ; with cyclopropan on the N atom) was the most active compound and showed eightfold to 88‐fold more potent activity than the standard drug ciprofloxacin against E .…”
Section: Synthetic Derivatives Of Flavonoidsmentioning
confidence: 99%
“…Hence, the prevention of biofilms is of utmost importance for modern medicine. The fact is that subinhibitory concentration of various antimicrobial agents possesses inhibitory effects on biofilm formation by different microorganisms [30,31]. On the other hand, it has also been reported that subinhibitory concentrations of some antimicrobial agents even enhance biofilm formation, for example erythromycin, nafcillin, quinupristin-dalfopristin, tetracycline and vancomycin on staphylococcal biofilm formation [32].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of sub-MICs of three newly synthesized chalcones on methicillin-resistant S. aureus were examined. Both biofilm formation and adherence to human fibronectin were reduced, as well as the release of EPS [87].…”
Section: Subinhibitory Amounts Of Plant Substancesmentioning
confidence: 99%